Preliminary Study of Dynamic Cerebral Autoregulation in Acute Ischemic Stroke: Association With Clinical Factors - Ma, Hongyin; Guo, Zhen-Ni; Jin, Hang; Yan, Xiuli; Liu, Jia; Lv, Shan; Zhang, Peng; Sun, Xin; Yang, Yi (Frontiers in Neurology, 2018)
Background and Purpose: Dynamic cerebral autoregulation (dCA) is probably impaired in the acute and even subacute phases after acute ischemic stroke (AIS); however, the relationship between relevant clinical factors and dCA after AIS has not been investigated. The identification of possible determinants may therefore provide potential therapeutic targets to improve dCA in AIS. Methods: This study enrolled 67 consecutive patients diagnosed with AIS within 3 days from symptom onset. Serial measurements were performed 1–3 days (measurement 1) and 7–10 days (measurement 2) after the onset. Middle cerebral artery blood flow velocities and simultaneous arterial blood pressure (ABP) were recorded continuously with transcranial Doppler combined with a servo-controlled finger plethysmograph. Transfer function analysis was used to derive dCA parameters, phase difference (PD), and coherence in low-frequency range (0.06–0.12 Hz). Univariate and multivariate linear regression analyses were conducted to determine the relationship between clinical factors and PD within the two time points of measurements. Multivariate logistic regression was performed to reveal the relationship between PD and clinical outcomes. Results: Bilateral PD was significantly lower (indicating impaired dCA) in AIS patients, both in measurement 1 and measurement 2 when compared with those of healthy controls (all P < 0.001). After controlling for relevant clinical factors, in measurement 1, age (β = −0.29, P = 0.01), recombinant tissue plasminogen activator (rt-PA) intravenous thrombolysis (β = 0.25, P = 0.034), subtype of large-artery atherosclerosis (LAA) (β = −0.31, P = 0.007), and uric acid level (β = −0.32, P = 0.009) were significant independent predictors of ipsilateral PD. In measurement 2, subtype of LAA (β = −0.28, P = 0.049) and uric acid level (β = −0.43, P = 0.005) were still significant predictive values for ipsilateral PD. After adjusting for age and National Institutes of Health Stroke Scale at admission, ipsilateral PD >35.37° in measurement 2 was independent predictor of good clinical outcomes (adjusted OR = 6.97, 95% CI: 1.27–38.14, P = 0.03). Conclusion: DCA was sustained to be bilaterally impaired in the acute and even subacute phase after AIS. Patients who receiving rt-PA thrombolysis tended to have a better dCA in the acute phase. Increasing age, subtype of LAA, and higher uric acid level had prognostic value for disturbed autoregulation. A relatively preserved dCA may predict good clinical outcomes.